2018
DOI: 10.1111/den.12994
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical algorithms for predicting common bile duct stones have only moderate accuracy

Abstract: Three diagnostic algorithms commonly used for predicting CBD stones have comparable but only moderate accuracy. Further research is warranted to improve risk stratification of patients with suspected CBD stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
7
0
3
Order By: Relevance
“…Recently, with a widely open data movement, the vigorous development of deep learning methods have greatly improved ability of computer-assisted diagnosis method [2]. There are three major tasks in medical image analysis, which are image classification, detection and segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with a widely open data movement, the vigorous development of deep learning methods have greatly improved ability of computer-assisted diagnosis method [2]. There are three major tasks in medical image analysis, which are image classification, detection and segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…26 While some suggest that hyperbilirubinemia reflects true biliary obstruction at presentation of acute cholecystitis and pancreaticobiliary disease, another hypothesis is that it may be reactive to hepatocellular injury in the acute setting. 7,10,11,27,28 In our study, the majority of our cohort had abnormal biliary enzymes at presentation (80.6% elevated GGT, 73.5% elevated bilirubin and 55.5% elevated ALP), although most of these patients had no choledocholithiasis.…”
Section: Discussionmentioning
confidence: 51%
“…[7][8][9] However, these are of mediocre accuracy and there is no current generalized consensus on the ideal utilization of MRCP. 10 The purpose of this study was to evaluate the yield of urgent MRCPs performed for in-hospital and emergency department (ED) patients presenting with acute pancreaticobiliary disease, and to determine potential predictors of a positive study. This was done via scrutinizing multiple variables, including patient age, gender, preceding pancreaticobiliary enzymes, and results of initial US assessment.…”
Section: Introductionmentioning
confidence: 99%
“…The guideline recommended that endoscopy or surgery should be performed for high-risk patients to remove stones, while those patients with intermediate risk should further make a definite diagnosis by EUS or MRCP [14]. However, several studies showed unsatisfactory diagnostic accuracy of ASGE guideline for predicting CBD stones [15,16]. MRCP is widely accepted as a non-invasive diagnostic method with high sensitivity and specificity, but it is time-consuming, relatively expensive, and its diagnostic accuracy mainly depends on the image quality and radiologist's experience.…”
Section: Discussionmentioning
confidence: 99%